New patterns of menstrual disorders' treatment - unification of the method - О. В. Грищенко; В. В. Бобрицкая (Publishing House TRILIST, 2019)
Effective treatment of menstrual cycle disorders, elimination of polypragmasia, and unification of the method in various types of menstrual disorders is an important task of modern science and practice. The aim of the study was to optimize the treatment of menstrual disorders with drugs of plant origin, by comparing the clinical efficacy of TazalokTM and Vitex agnus-castus. Design: a comparative study. Materials and methods. Under the supervision there were 60 patients aged 23-37 years with various forms of menstrual disorders, divided into two groups of 30 people, in accordance with therapy. Patients of the main group I received TazalokTM for treatment of menstrual disorders, 45 drops 2 times a day, patients II (comparison group) received 40 drops of Vitex agnus-castus 1 time per day. The course of therapy was 3 months. The main group and the comparison group were divided into two subgroups of 15 patients, in accordance with the peculiarities of the menstrual disorders. Subgroup IA of main group - patients with heavy bleeding during the menstrual period, IВ - patients with scanty menstruation. In the comparison group: IІА - heavy menstrual bleeding, IIB - meager menstrual bleeding. All patients underwent a hormonal study before and after 3 months of treatment, sonographic monitoring, evaluation of subjective complaints. Results. There was normalization of the level of steroid hormones, the thyroid gland hormones. A significant decrease in cortisol levels was in patients taking TazalokTM. Sonographic characteristics of the pelvic organs, mammary glands, and the thyroid gland in patients treated with TazalokTM showed a positive trend, the disappearance of the pathological vascularization of target organs. Decrease in complaints by 2-3 weeks of taking. Conclusion. TazalokTM is an effective medicine for the treatment of various clinical forms of menstrual cycle disorders, has a wider range of effects compared with Vitex agnus-castus.